Has globalization changed the international transmission of U.S. monetary policy? - Maximilian Boeck; Lorenzo Mori (Norges Bank, 2024)
We estimate a time-varying parameter vector autoregression to examine the evolution of international spillovers of U.S. monetary policy in light of increasing globalization in real and financial markets. We find that the adverse international effects of a U.S. tightening have substantially increased over the past three decades, peaking during the Great Recession. Based on a cross-country analysis and counterfactual simulations, we argue that such amplification can primarily be attributed to the surge in trade integration, while the role of rising financial integration in explaining the time-variation is limited.
hdl:11250/3166793
Keywords: C32; E32; E52; F42; F62; 330; Monetary policy; international Spillovers; Monetary Policy; International Spillovers; TVP-VARs